PENGARUH PEMBERIAN PUPUK ORGANIK CAIR NASA DAN ASAL BAHAN TANAM TERHADAP PERTUMBUHAN DAN HASIL TANAMAN STROBERI (Fragaria sp) - Marisi Napitupulu, Maryani, Puji Astuti, (Universitas 17 Agustus 1945 Samarinda, 2013)
The purposes of the research was to know about: (1) the effect of giving organic fertilizer nasa and the origin of planting material on the growth and crop of strawberry plant; (2) the best result of origin planting material on the growth of strawberry plant; and (3) the best interaction of giving fertilizer with origin planting material to the growth and crop of strawberry plant.The research was conducted in Faperta garden of 17 August 1945 University, Samarinda City, East Borneo Province. It took about 6 months from March to August 2012. The completely randomized design was employed for this research with factorial analysis 3 x 4 and 3 replications. The fist factor is the origin of planting material which consists of 3 levels, namely the fist stolon (s1), second stolon (s2), and third stolon (s3). The second factor is the concentration of liquid organic fertilizer nasa, which consists of 4 levels : without poc nasa (n0), poc nasa 2,5 ml/liter of water (n1), poc nasa 5 ml/liter of water, and 7,5 ml/liter of water.The treatment of giving liquid organic fertilizer nasa is different and not visible to the growth of plant height (4, 8, and 12 weeks after planting), the number of stolon tillers, and the number of fruits. It is different and visible on the age of plant as it is growing first stolon, and fresh fruits weight per fruit. While at the age when the plant is flowering shows the result, different and very visible. The treatment of origin of planting material is different and not visible to the increase of plant height 8 weeks after planting, the fruits weight per fruit, and the number of fruits. The parameter of plant height 4 weeks after planting, the number of stolon tillers, and the age of plant when it is flowering, the treatment of origin planting material show the different and very visible. The interaction of giving liquid organic nasa and the origin of planting materials, from all parameter is showed the different and not visible.